International trade and migrant networks: Is It really about qualifications? - Joan A. Martín-Montaner; Francisco Requena Silvente; Guadalupe Serrano (Estudios de Economía, 2014)
Personal characteristics of migrants could help to strengthen the impact of migrant networks on bilateral trade. While most of the attention has been focused on immigrants' educational attainment, this paper focuses on the relevance of the tasks carried out by migrants. Our empirical results confirm that the existence of a large number of foreign-born workers with managerial duties is critical to explain the reduction of transaction costs caused by migrant networks.
Keywords: F14; F22; 330; international trade; migration; networks; gravity equation